Trends in Ecotourism Research in Indonesia: Basic Analysis of the Development of Ecotourism-Based Teaching Materials - Hamidi Hamidi; Agus Abhi Purwoko; Agil Al Idrus; Ahmad Harjono; Joni Rokhmat; A.A. Sukarso (Postgraduate, University of Mataram, 2023)
Currently and in the future, tourism is expected to make the biggest contribution to increasing the country's foreign exchange in the government's efforts to realize people's welfare and prosperity. One form of tourism product as a derivative of the concept of sustainable tourism development is the concept of ecotourism development. This study aims to map the research that has been carried out related to ecotourism in Indonesia. Data were obtained from scientific papers published on Google Scholar from 2010-2022 and there were 985 published scientific papers consisting of 968 from journals, 16 from proceedings, and 11 from books. Bibliometric analysis was carried out using the Vos Viewer application. The results of the study show that Indonesia has many tourist areas that can be developed into ecotourism areas, and these can be used as objects of research on ecotourism, but during the last 10 years research has only been conducted in a few areas. In addition, research on the same thing is often carried out in different research locations. This is the weakness of research on ecotourism in Indonesia. Thus, it is concluded that there are still many areas and keywords that are different and related to the concept of ecotourism which can be used as research subjects in Indonesia. research on the same thing is often done with different research locations. This is the weakness of research on ecotourism in Indonesia. Thus, it is concluded that there are still many areas and keywords that are different and related to the concept of ecotourism which can be used as research subjects in Indonesia. research on the same thing is often done with different research locations. This is the weakness of research on ecotourism in Indonesia. Thus, it is concluded that there are still many areas and keywords that are different and related to the concept of ecotourism which can be used as research subjects in Indonesia